Protein-mediated wool-ball-like copper sulfide as a multifunctional nanozyme for dual fluorescence "turn-on" sensors of cysteine and silver ions. Issue 39 (10th September 2020) - Liu, Yan; Jin, Haijia; Zou, Wenting; Guo, Rong
Abstract : Protein-mediated wool-ball-like copper sulfide as a multifunctional nanozyme for dual fluorescence "turn on" sensors of cysteine and silver ions. Abstract : Developing a multifunctional nanozyme based biosensor with a convenient approach and high reliability is of vital interest for multiplex detection. In this study, wool-ball-like copper sulfide (WBLCS) was obtained facilely using an amphiphilic protein. The acidic amino acid residues and the amphiphilic properties of protein molecules play cooperative roles in the fabrication of hierarchical nanostructures. Unlike copper sulfide with irregular morphologies, the single component WBLCS acts as a multifunctional nanozyme possessing both superior cysteine oxidase- and peroxidase-mimicking activity. Fascinatingly, the addition of silver ions can significantly enhance the performance of the cascade system at a very low fluorescence substrate concentration. Based on this, dual fluorescence "turn on" sensors of cysteine and silver ions with extremely high sensitivity and selectivity are developed. This is the first report to explore multiple fluorescence "turn on" sensing systems based on one single nanozyme. Hence, the present finding has significant implication towards the design of superstructured nanozymes combining different multi-functionalities at the nanoscale for sensing multiplex target molecules sensitively and selectively in practice.